ANALISIS RETURN ON EQUITY DALAM MENILAI HARGA SAHAM PT. ASTRA INTERNASIONAL. TBK - Reni El Vionita (Sekolah Tinggi Ilmu Ekonomi Tribuana, 2020)
This study aims to find out how return on equity in assessing the stock prices of PT ASTRA INTERNATIONAL Tbk listed on the Indonesia Stock Exchange. The method used in this study is a qualitative descriptive. Data collection tecniques used are the financial statements for the period 2014 to 2018. Based on the analysis and discussion of the research results it is known that company profits continue to experience this because income earnings are decreasing every year, and equity always increases due to income stock that continues to grow. Return on equity (ROE) at PT. Astra Internasional Tbk. From the calculation of return on equity analysis, in 2014 a percantage of 37,2% was obtained, in 2015 it decreased to 26,2%, and in 2016 the value of return on equity (ROE) again rosr to 24,9%, while in 2017 the vaule of return on equity (ROE) again rose to 25,6%, in 2018 it has again decreased to 22,8%. From these results it is stated that return on equity (ROE) of PT.Astra Internasional Tbk has decreased every year, but the share price continues to rise annually. Based on financial reports for 5 years, from 2014 to 2018 and besed on this research, it was found that return on equity (ROE) has a positive relatoinship with an avarage value of 27,3%, the rest is influenced by other factors beyond the calculation if return on equity (ROE) not discussed in this thesis.